Ribosomal Protein S3: A Multifunctional Target of Attaching/Effacing Bacterial Pathogens - Gao, Xiaofei; Hardwidge, Philip R. (Frontiers in Microbiology, 2011)
The extraribosomal functions of ribosomal proteins have drawn significant recent attention. Ribosomal protein S3 (RPS3), a component of the eukaryotic 40S ribosomal subunit, is a multifunctional protein that regulates DNA repair, apoptosis, and the innate immune response to bacterial infection. Here we the review the latest findings about RPS3 extraribosomal functions, with special emphasis on their relation to microbial pathogenesis and enteropathogenic Escherichia coli.